Infant attraction: why social bridging matters for female leadership in Tibetan macaques. Issue 6 (13th June 2020) - Wang, Xi; Xia, Dong-Po; Sun, Lixing; Garber, Paul A; Kyes, Randall C; Sheeran, Lori K; Sun, Bing-Hua; Li, Bo-Wen; Li, Jin-Hua
Abstract: Leadership is a key issue in the study of collective behavior in social animals. Affiliation–leadership models predict that dyadic partner preferences based on grooming relationships or alliance formation positively affect an individual's decision to follow or support a conspecific. In the case of many primate species, females without young infants are attracted to mother–infant dyads. However, the effects of mother–infant–female associations on affiliation–leadership models remain less clear. In free-ranging Tibetan macaques Macaca thibetana, we used social network analysis to examine the importance of "mother-infant-adult female" social bridging events as a predictor of who leads and who follows during group movement. Social bridging is a common behavior in Tibetan macaques and occurs when 2 adults, generally females, engage in coordinated infant handling. Using eigenvector centrality coefficients of social bridging as a measure of social affiliation, we found that among lactating females, initiating bridging behavior with another female played a significant role in leadership success, with the assisting female following the mother during group movement. Among nonlactating females, this was not the case. Our results indicate that infant attraction can be a strong trigger in collective action and directing group movement in Tibetan macaques and provides benefits to mothers who require helpers and social support in order to ensure the safety of their infants. Our study provides new insights into the importance of the third-party effect in rethinking affiliation–leadership models in group-living animals.